András Illyés’s St. Martin sermons - Maczák, Ibolya (Verbum – Analecta Neolatina, 2017)
Péter Pázmány never published a single sermon about saints of the Árpád dynasty; however, he published one about the canonized King Ladislaus, although not under his own name: Transylvanian bishop András Illyés published Pázmány’s only speech written for St. Martin’s day as three Saint Ladislaus sermons under the title Megrövidittetett ige [The divided word] in the 1692 volume of his five-volume collection of sermons. András Illyés’s work as a compiler was further affected by his editorial principles. In his collection of sermons about saints, there is a sermon about St. Martin, but it is not based on Pázmány’s speech: Illyés clearly worked with a range of sources in compiling his volumes. New findings also allow for identifying texts with Italian sources, among them texts which Illyés translated into Hungarian from Giuseppe Mansi’s collection, Prontuario sacro per tutte le solennità, and published in abridged form under his own name.